Genetic Modifications of Developmental Dyslexia and Its Representation Using In Vivo, In Vitro Model - Zakiyyah, M.M. Zaki; Siti Atiyah, Ali; Mazira, Mohamad Ghazali; Faidruz, A. Jam (Higher Education Press, 2024)
Dyslexia is a genetic and heritable disorder that has yet to discover the treatment of it, especially at the molecular and drug intervention levels. This review provides an overview of the current findings on the environmental and genetic factors involved in developmental dyslexia. The latest techniques used in diagnosing the disease and macromolecular factors findings may contribute to a higher degree of development in detangling the proper management and treatment for dyslexic individuals. Furthermore, this review tried to put together all the models used in the current dyslexia research for references in future studies that include animal models as well as in vitro models and how the previous research has provided consistent data across many years and regions. Thus, we suggest furthering the studies using an organoid model based on the existing gene polymorphism, pathways, and neuronal function input.